PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP PENINGKATAN PENGUASAAN KONSEP SISWA KELAS XI SMK PADA MATERI FLUIDA STATIS - Sudirman Sudirman (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
The advanced Research goal is to Obtain a picture of the use of models to enhance problem-based learning concept mastery of vocational students in class XI and the static fluid material to Obtain a picture of students' responses to the model of problem based learning. The method used is a quasi-experimental design "pretest-posttest control group design" Implemented in class XI in one vocational school in Sambas district for school year 2011/2012. The data was collected using the initial test and final test for the control concept of students as well as a questionnaire to find out students' responses to the model of problem based learning. Based on the analysis of the data obtained by the average N-gain students' mastery of the concept of 0:33 to 0206 for the experimental class and control class. The results of hypothesis testing using two independent samples t test with SPSS 16 shows That Increasing mastery of the concept of learning by students WHO follow the model of problem based learning method is higher than the experimental inquiry of the which follows the learning of students with problem based learning with practical methods acre free. Concluded That the learning by problem-based learning by experimentation can significantly improve students' mastery of concepts compared to the free practice